Cooperation for a peaceful and sustainable world - Junsheng, Li; Bo, Chen; Na, Hou (Emerald, 2013)
Part 2 of the Cooperation for a peaceful and sustainable world volume, brings together some of the leading researchers on peace science. Chapters discuss issues including, but not restricted to, military expenditure and economics in China, India and Pakistan, Peace science in South East Asia, and approaches to anti-terrorism.
Includes index.
Keywords: Political Science -- General.; Political science & theory.; Peace -- Economic aspects.; Peace-building -- Economic aspects.; Econometric models.; elektronické knihy; electronic books